1995
DOI: 10.1111/j.1442-2026.1995.tb00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Triage nurse‐initiated X‐rays for limb injuries are accurate and efficient

Abstract: Objectives To estimate the potential reduction in waiting times for patients resulting from triage nurse‐initiated X‐rays. To compare the pattern of X‐ray ordering by triage nurses and medical staff. To estimate the accuracy of triage nurse‐initiated X‐rays. Method Prospective, blinded descriptive/comparative study with nursing intervention on an ‘intention to treat’ basis. Results Triage nurse‐initiated X‐rays would have identified 96% of fractures. Nurses would have ordered fewer X‐rays than doctors with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…The results of Kelly, McCarthy, Richardson, Parris, and Kerr (1995) suggested that the average timesavings for the patient could be in the order of 45 min. Others studies found that the timesavings for patients ranged from 8 to 60 min when nurses initiated radiographs at the point of triage (Davies, 1994, Macleod & Freeland 1992Parris et al, 1997).…”
Section: Wait Times: Patient and Staff Satisfactionmentioning
confidence: 96%
“…The results of Kelly, McCarthy, Richardson, Parris, and Kerr (1995) suggested that the average timesavings for the patient could be in the order of 45 min. Others studies found that the timesavings for patients ranged from 8 to 60 min when nurses initiated radiographs at the point of triage (Davies, 1994, Macleod & Freeland 1992Parris et al, 1997).…”
Section: Wait Times: Patient and Staff Satisfactionmentioning
confidence: 96%
“…Hence, the number and timing of laboratory-confi rmed cases were unrepresentative of the wider outbreak. In contrast, laboratory-supported infl uenza surveillance undertaken in parallel with diagnostic testing provided monitoring of the course of the outbreak relatively free of these effects ( Figure 1) and, as described elsewhere, enabled direct comparison of the outbreak with >10 years of seasonal infl uenza (3,7,8).…”
Section: Outbreak Monitoringmentioning
confidence: 99%
“…Hence, the number and timing of laboratory-confirmed cases were unrepresentative of the wider outbreak. In contrast, laboratory-supported influenza surveillance undertaken in parallel with diagnostic testing provided monitoring of the course of the outbreak relatively free of these effects (Figure 1) and, as described elsewhere, enabled direct comparison of the outbreak with >10 years of seasonal influenza ( 3 , 7 , 8 ). …”
Section: Outbreak Monitoringmentioning
confidence: 99%